Ground states for the pseudo-relativistic Hartree equation with external potential. Issue 1 (30th January 2015) - Cingolani, Silvia; Secchi, Simone
Abstract : We prove the existence of positive ground state solutions to the pseudo-relativistic Schrödinger equation where N ≥ 3, m > 0, V is a bounded external scalar potential and W is a radially symmetric convolution potential satisfying suitable assumptions. We also provide some asymptotic decay estimates of the found solutions.